(untitled) (Al-Aasar, 2026)
The question of how the Islamic intellectual tradition has understood and responded to atheism is one that spans more than a thousand years of continuous scholarly engagement. This article examines that tradition through a comparative lens, bringing together four classical Muslim scholars, Al-Maturidi, Al-Ghazali, Fakhr al-Din al-Razi, and Ibn Taymiyyah, and four contemporary Muslim intellectuals, Hamza Tzortzis, Muhammad Hijab, Dr. Shoaib Ahmed Malik, and Dr. Nazir Khan, to identify the epistemological commitments that unite them across the centuries and the genuine innovations that distinguish the modern from the classical period. Drawing on a qualitative and comparative methodology, the article argues that despite the vast difference in historical context, all eight scholars share three foundational epistemological convictions: the rejection of pure empiricism as a sufficient basis for answering questions of ultimate meaning; the use of dialectical inversion to expose the internal incoherence of atheistic reasoning; and the conviction that reason and divine revelation are fully compatible. At the same time, the article identifies real and significant differences, most importantly the emergence of the philosophy of science as an indispensable arena of engagement, the transformation of audience and medium, and the cross-confessional intellectual openness of the contemporary period. The article concludes that the Islamic epistemological response to atheism is not a medieval relic but a living, adaptive intellectual tradition, one that has met every challenge it has faced with rigour and confidence and remains more than equal to the demands of the present age.